Gliflozins for the prevention of stroke in diabetes and cardiorenal diseases: A meta-analysis of cardiovascular outcome trials. Issue 39 (1st October 2021) - Zhao, Li-Min; Huang, Jia-Nan; Qiu, Mei; Ding, Liang-Liang; Zhan, Ze-Lin; Ning, Jie
Abstract: Background: Individual randomized trials are not powered to assess the relationship between use of sodium–glucose transporter 2 inhibitors and risk of stroke. We sought to explore this issue by a meta-analysis incorporating relevant trials including several latest trials. Methods: Cardiovascular outcome trials of gliflozins were included. Primary outcome was stroke, while secondary outcome was major adverse cardiovascular events (MACE), which was a composite of stroke, myocardial infarction, or cardiovascular death. Meta-analysis was conducted stratified by with/without chronic kidney disease (CKD), with/without heart failure (HF), and with/without atherosclerotic cardiovascular disease (ASCVD), and stratified by different gliflozins. Results: We included 9 trials in this meta-analysis. Compared with placebo, gliflozins significantly lowered stroke (hazard ratio [HR] 0.68, 95% confidence interval [CI] 0.55–0.84) and MACE (HR 0.77, 95% CI 0.69–0.86) in type 2 diabetes (T2D) patients with CKD, but did not significantly affect stroke (HR 1.00, 95% CI 0.86–1.16) and MACE (HR 0.94, 95% CI 0.86–1.02) in T2D patients without CKD. Gliflozins had no significant effects on the stroke risk (HR 0.94, 95% CI 0.82–1.07) in T2D patients regardless of HF status ( P subgroup = .684) and ASCVD status ( P subgroup = .915), but significantly lowered MACE (HR 0.89, 95% CI 0.83–0.96) in T2D patients regardless of HF status ( P subgroup = .428) and ASCVD status ( P subgroup = .423). Canagliflozin (HR 0.84, 95% CI 0.69–1.01) showed the trend of a reduction in the stroke risk versus placebo, and sotagliflozin (HR 0.73, 95% CI 0.54–0.98) significantly lowered the stroke risk; whereas the other 3 gliflozins did not significantly affect that risk. Ertugliflozin (HR 0.97, 95% CI 0.85–1.11) had no significant effects on the MACE risk, whereas the other 4 gliflozins significantly lowered that risk. Conclusions: Gliflozins, especially canagliflozin and sotagliflozin, should be recommended in T2D patients with CKD to prevent stroke. Most gliflozins lower the risk of MACE in T2D patients regardless of HF status and ASCVD status, whereas ertugliflozin is not observed to lower that risk. Abstract : Supplemental Digital Content is available in the text